Answer:
E) ab + ab
Explanation:
The following options are missing:
A) 2a + b
B) ab + 2a
C) 5a + 6b
D) ab + 2b
E) ab + ab
An expression is even when f(x) = f(-x). In this case, the arguments are a and b. Let's suppose a = 1, b = 1 and analyze every option:
A) 2a + b = 2*1 + 1 ≠ 2*(-1) + (-1)
B) ab + 2a = 1*1 + 2*1 ≠ (-1)*(-1) + 2*(-1)
C) 5a + 6b = 5*1 + 6*1 ≠ 5*(-1) + 6*(-1)
D) ab + 2b = 1*1 + 2*1 ≠ (-1)*(-1) + 2*(-1)
E) ab + ab = 1*1 + 1*1 = (-1)*(-1) + (-1)*(-1) -> this is satisfied for every integers a and b